G647(P) Debriefing the debriefer – a technique in peer-review observation to ensure debrief quality assurance. (May 2019) - Reunis, E; Bloomfield, C; Finegan, H; Zahir, F; Bandhakavi, M; Chilvers, J
Abstract : Aim: It is widely recognized that debriefing is one of the most important aspect of simulation-based education (Motola et al, 2013; ASPiH 2016). To quality assure debriefs of our simulation courses, including the Paediatric simulation course, we devised a technique in peer-review observation. Whether novice or experienced debriefers, 'Debriefing the Debriefer' initiative allows faculty to reflect on and evaluate their debriefing skills. The aim of this study is to evaluate this initiative: Is there a demand for it? Does it increase faculty debriefing confidence? Will it influence future debriefs? Methods: Prior to piloting the initiative, we carried out a pan-faculty survey to evaluate demand. We piloted the initiative for 10 faculty members, a mixture of both novice and experienced debriefers. They were informed ahead of time their debriefs would be observed by another faculty member. Time was allocated at the end of simulation sessions, once the learners had left, for a peer-led debrief of the debrief. Feedback was standardised using Nunn&Winston (2015) Feedback Form – Table 1 : The post-initiative survey evaluated the impact on faculty perceived confidence in debriefing. Results: 90% of responders reported they would find feedback on their debriefs useful. Of the 10 faculty members in the pilot initiative, 6 completed the post-initiative survey. Analysis demonstrated an overall increase in debriefing confidence (table 2 ): 100% reported feedback would influence future debriefs and 100% would like to continue receiving feedback on debriefs. Conclusion: Analysis confirmed there is a demand for post-debrief feedback, and the initiative resulted in an increase confidence in debriefing. We believe this initiative helps to ensures quality assurance of debriefs – the centerpiece of simulation-training. References: ASPiH Simulation-based education in healthcare Standard Framework and Guidance. 2016. Motola I, et al. Simulation in health healthcare education: a best evidence partical guide. AMEE Guide No. 82. Med Teach2013Oct;35(10):e1511–30. Nunn A, Winston I. Debriefing Feedback Form2015.